G405(P) Safety and Clinical Effectiveness of Chloral Hydrate for Painless Procedural Sedation in Children. (7th April 2014) - Alotaibi, B; Sammons, H; Choonara, I
Abstract : Aims: To analyse all studies discussing effectiveness and safety (adverse events (AEs)) of chloral hydrate as a sedative drug in children undergoing diagnostic and/or treatment painless procedures. Methods: A systematic literature review of MEDLINE (1948–January 2012), EMBASE (1980–January 2012), COCHRANE (from 1974 to January 2012) and CINAHL (from 1974 to January 2012). The search terms used included "chloral hydrate" and "children or infant or pe*diatric* or neonate or adolescence or adolescences or adolescent" and "sedation". The search was limited to the studies that assessed chloral hydrate safety and efficacy in children, up to 18 years, undergoing painless procedures. Retrieved articles were reviewed and data were abstracted using standardised data collection. Trial quality was assessed using the Jadad score for RCTs and STROBE scoring checklist for observational studies. Results: Of the 76 articles identified, 60 met the inclusion criteria for analysis of AEs. Hypoxia is the most commonly reported AE, incidence rate of 5.1 per 100 children. Many cases (528) were mild (SpO2 90–95%), 3.5 per 100. Moderate hypoxia (SpO2 <90%) was seen in 247 cases, 1.6 per 100, and was completely reversible after using simple manoeuvres, such as supplemental oxygen therapy. There were no deaths, however eight serious respiratory AEs all required medical interventions and/or hospitalisation. Hypoxia was more common in infants under two years (8.0 per 100 children). The second most frequently reported adverse event was vomiting, risk of 2.9 per 100 children. 58 studies met the inclusion criteria for the analysis of clinical effectiveness. The success rate of painless procedural sedations was variable (range 50%–100%). The success rate (up to 100%) was higher for shorter imaging procedures such as CT imaging versus (81%) for MRI. Conclusions: The systematic review suggests that chloral hydrate is a safe and effective agent for painless procedural sedation. The moderate incidence of hypoxia emphasises the importance of monitoring children during sedation, especially infants, and that the sedation should be conducted by a practitioner confident in resuscitation.